(untitled) (World Bulletin of Social Sciences, 2025)
Beach tourism in Lagos State is characterized by intense competition between public and private tourist beaches. Although public beach services are more affordable, however, private beaches appear to draw more tourists/visitors than their public counterparts. This study was therefore undertaken to ascertain if the observed variation in the visitor-drawing ability of public and private beaches could be explained by their beach service strategies and the type of destination experience they create for their visitors. The study was a comparative research in which a descriptive survey design was adopted whereby 246 beach visitors/tourists at public and private beaches in Lagos participated in the study, drawn through the convenience sampling method. Primary data were collected through the questionnaire technique supplemented by secondary data. Research questions were analyzed with the descriptive statistics of mean scores and standard deviations while the null hypotheses of the study were tested using the independent sample test. The findings revealed that the services strategies (hospitality service delivery, activities, water sport equipment rentals and visitors’ safety measures of private beaches were significantly better and generated more satisfying destination experience for visitors than those of the public beaches. It was recommended that management of the public beaches should introduce innovative products/ services water sport equipment rentals and beach activities in order to draw more tourists/visitors. Private beaches should maintain or improve on current available services and constantly review their offerings through regular interactions with visitors.